Latvia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper and Statistical Appendix highlights that the strong economic expansion in Latvia that began in 1996 and accelerated in the following year reversed sharply in mid-1998 as a result of both external and domestic shocks. The initial expansion was fueled by accelerating domestic private and public demand, as well as growing demand for Latvia's output in both new, mostly European Union, and the traditional Commonwealth of Independent States markets. Domestic consumer and investment demand were supported by growing real incomes and tax revenues and pent-up demand carried over from previous years.